The Tragedy of the Commons, Livestock Cycles and Sustainability. - Fafchamps, M (1998)
This paper revisits the tragedy of the commons and examines the conditions under which externalities contribute to livestock cycles. Using a stylised intertemporal model capturing the main characteristics of African livestock producers, we show that externalities magnify livestock cycles triggered by occasional droughts. This is true even when producers are fully rational. Two forces fuel such cycles: producers' concerns with consumption smoothing; and expected capital gains when demand for livestock products is inelastic. Implications regarding African livestock production are discussed.